(untitled) (Bangladesh Rice Journal, 2017)
Assessment of genetic diversity and molecular characterization among rice landraces of Bangladesh is important for their identification. Genetic diversity of 96 Aman (rainfed, partially irrigated) rice landraces of Bangladesh were evaluated using eight SSR markers to characterize the landraces and also to establish the sovereignty of Bangladeshi rice gene pool. A total of 159 alleles were detected. The number of alleles per locus ranged from 13 (RM60, RM237) to 34 (RM163), with an average of 19.88. The polymorphism information content (PIC) which ranged from 0.86 (RM237) to 0.95 (RM163) with an average of 0.90 revealed much variation among the studied landraces. RM163 was the best marker for identification and diversity estimation of Aman rice landraces as revealed by PIC values. The allele frequency ranged from 8.33% (RM163) to 22.92% (RM60, RM125) with an average of 15.89. The UPGMA dendrogram based on Neis genetic distance revealed seven distinct clusters with a similarity coefficient of 0.09. The two-dimensional graphical view of Principal Coordinate Analysis (PCoA) revealed that the landraces Pankaij, Lotha, Chinigura, Patjag, Chinikanai, Badshabogh, Panati, Jirasail, Joria, Dudhmoni, Jhingasail were found far away and distributed around the centroid of the cluster. The findings of this study are useful for landraces identification to assist plant breeders in selecting suitable genetically diverse parents for breeding programmes. Bangladesh Rice j. 2016, 20(2): 1-11